COMBINATION OF AES ALGORITHM WITH BLOWFISH ALGORITHM FOR FILE ATTACHMENT AT E-MAIL SENDING - Yongki Iswo; Poltak Sihombing (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Data security in the delivery of online file becomes very important in the world of information itself. One way that can be done for the security of the data is to perform encryption before the data is sent. Cryptographic message encoding divided into two symmetric and asymmetric. Kriptogarfi AES (Advanced Encryption Standard) is a symmetric cryptographic algorithms means that the key used in the encryption process is the same as the key to the decryption process. The analysis concludes theory, AES encryption process is designed to make the process of encoding in secret with no security level of complexity linear with time as efficiently as possible through the use of processes of transformation of light in the implementation. Aside from the AES algorithm, Blowfish algorithm is also a symmetric cryptographic algorithm. Theory analysis shows that Blowfih a cryptographic algorithm that uses a key with variable length provided that no more than 448-bit. Blowfish also combine non-reverse function f, keydependent S-Box, dun Feistel network. The process of encryption and decryption using the ECB and CBC operation has the same worst case is O (n). In this study the authors combine these two algorithms in the security of a file attachment in an email that is expected to increase the security file.